Governance along the new silk road in Southeast Asia and Central and Eastern Europe: a comparison of ASEAN, the EU and 17+1 - Gerstl, Alfred (Penerbit Universiti Kebangsaan Malaysia, 2020)
Southeast Asia and Europe are key regions for the implementation of China’s Belt and Road Initiative (BRI). A comparison of China’s attempt to promote the BRI in both regions reveals that China acts both as a norm-setter and norm-taker. Both the Association of Southeast Asian Nations and the European Union which established distinct regional governance systems perceive China’s growing ability to set norms in their region as a strategic threat. However, the 17+1 (formerly 16+1) cooperation format, established by China in Central and Eastern Europe as an umbrella for its bilateral relations, is embedded in the EU’s governance system. In Southeast Asia, China cooperates with the individual governments on a bilateral base, but also utilizes the existing ASEAN infrastructure schemes. The article argues that China needs to be better included in the established international and regional governance mechanisms. It concludes that after mutual compromises of the participants and reforms the New Silk Road could function as a respected framework for multilateral collaboration that complements, but does not replace the existing governance structures and principles.